Transcriptome analysis to explore the mechanism of downregulated TNIK influencing the effect of risperidone - Yuan, Ruixue; Li, Yaojing; Li, Xiangyi; Fu, Yingmei; Ning, Ailing; Wang, Dongxiang; Zhang, Ran; Yu, Shunying; Xu, Qingqing (Frontiers in Pharmacology, 2024)
Risperidone is one of the most reliable and effective antipsychotics for schizophrenia treatment. However, the mechanism of action of risperidone is not yet fully understood. Traf2 and Nckinteracting protein kinase (TNIK), a schizophrenia susceptibility gene, is associated with risperidone treatment response. Our previous in vitro experiments confirmed that downregulated TNIK affected the effect of risperidone on downstream targets. However, the effect of downregulated TNIK on risperidone-induced molecular expression remains to be further explored. Hence, transcriptome analysis was performed on U251 cells subjected to risperidone, TNIK siRNA, and no treatment, respectively. Compared to the no-treatment group, two groups of DEGs were screened out and then intersected with the schizophrenia-related genes to screen the cross-talk genes. Those DEGs were analyzed using GO and KEGG. STRING and Cytoscape were used to construct a protein-protein interaction (PPI) network for the cross-talk gene. The result showed that the parathyroid hormone synthesis, secretion, and action were significantly enriched after risperidone treatment. Downregulated TNIK could have an impact on the collagen-containing extracellular matrix, signaling receptor activator activity, and PI3K-Akt signaling pathway. Interestingly, bone mineralization function and calcium signaling pathway were enriched in the cross-talk genes. Additionally, FGFR2, FGF1, and FGFR might be the potential targets for TNIK affecting the effects of risperidone. In conclusion, the study indicated that risperidone primarily influences functions and/or pathways associated with bone metabolism, potentially contributing to the adverse effect of osteoporosis. Our study may offer a novel perspective on investigating the mechanisms underlying the adverse effects of risperidone.